1974
DOI: 10.1136/bmj.4.5942.444
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Assessment of Cardioselectivity of Beta-blocking Drugs

Abstract: Small though significant differences (P < 0-05) were found only between the changes in FEVy after placebo and the reductions after each drug at one, two, and three hours, and there was no significant difference beween the effects of the two drugs. This study supported the suggestion that betasympathetic stimulation contributes to the bronchodilatation evident during exercise. Moreover, it emphasizes the importance of assessing airway resistance both at rest and during exercise and of comparing the pulmonary ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…Although ,Iadrenoceptors are in the minority in the lung, animal experiments suggest they have functional importance (Carswell & Nahorski, 1983). In an earlier study, Kumana et al (1974) suggested that practolol did not reduce peak flow rate to the same extent as propranolol during exercise. Our study implies that some of this difference may have been due to partial agonist action.…”
Section: Discussionmentioning
confidence: 99%
“…Although ,Iadrenoceptors are in the minority in the lung, animal experiments suggest they have functional importance (Carswell & Nahorski, 1983). In an earlier study, Kumana et al (1974) suggested that practolol did not reduce peak flow rate to the same extent as propranolol during exercise. Our study implies that some of this difference may have been due to partial agonist action.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Kumana, Marlin, Kaye & Smith (1974) have shown that peak flow rate (PFR) increases with severe exercise in normal subjects. This has been used as a basis for assessing the cardioselectivity of /3-adrenoceptor blocking drugs.…”
Section: Cardioselectivitymentioning
confidence: 99%
“…The simultaneous effects of the drug on cardiovascular and respiratory function can then be compared with the control results and observations on cardioselectivity made. Initially Kumana et al (1974) compared propranolol, practolol and a placebo using this method, following the effects for 24 hours. They were able to show that both active drugs had a significantly greater effect on exercise heart rate than did placebo.…”
Section: Cardioselectivitymentioning
confidence: 99%
“…It is also difficult to measure selectivity quantitatively in patients with asthma where airways obstruction is unstable and the patient may be taking other treatment. Recent studies have used the post exercise increase in peak expiratory flow rate (PEFR) in normal subjects and compared the extent to which different,-adrenoceptor blocking drugs antagonize this effect but the increases in PEFR are small (Kumana, Marlin, Kaye & Smith, 1974;Kumana, Kaye, Leighton, Turner & Hamer, 1975;Oh, Kaye, Warrington, Taylor & Wadsworth, 1978) and the effects difficult to quantitate.…”
Section: Introductionmentioning
confidence: 99%